PENGARUH PENGGUNAAN MEDIA VIDEO ANIMASI TERHADAP KETERAMPILAN MENULIS TEKS PUISI SISWA KELAS VIII SMPN 23 PADANG - Hafizah, Farjul; Arief , Ermawati; Amir, Amril; Emidar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of animated video media on the poetry writing skills of eighth-grade students at SMPN 23 Padang. The research is grounded in theories regarding animated video media and poetry writing skills. Animated video media is an audiovisual learning tool that combines moving images, sound, text, and visual effects, thereby capturing students' attention and helping them grasp the material in a more concrete manner. This study employs a quantitative approach using a quasi-experimental method. The research design utilized is the Nonequivalent Group Pretest-Posttest Design, involving two sample groups: an experimental class and a control class. The study population consists of all eighth-grade students at SMPN 23 Padang, with a sample size of 64 students distributed across two classes. Purposive sampling was used as the sampling technique. Based on the data description, analysis results, and discussion presented in Chapter IV, it is concluded that the poetry writing skills of eighth-grade students at SMPN 23 Padang who did not use animated video media fell into the